2016
DOI: 10.1007/s12975-016-0496-0
|View full text |Cite
|
Sign up to set email alerts
|

Dimethyl Fumarate and Monomethyl Fumarate Promote Post-Ischemic Recovery in Mice

Abstract: Oxidative stress plays an important role in cerebral ischemia–reperfusion injury. Dimethyl fumarate (DMF) and its primary metabolite monomethyl fumarate (MMF) are antioxidant agents that can activate the nuclear factor erythroid-2-related factor 2 (Nrf2)/heme oxygenase-1 (HO-1) pathway and induce the expression of antioxidant proteins. Here, we evaluated the impact of DMF and MMF on ischemia-induced brain injury and whether the Nrf2 pathway mediates the effects provided by DMF and MMF in cerebral ischemia–repe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
88
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(92 citation statements)
references
References 73 publications
4
88
0
Order By: Relevance
“…Wu et al . reported that the Nrf2/ARE pathway activator myricetin lessened the production of ROS, decreased infarct volume, and reduced neuronal loss after ischemia (44, 45). This conclusion is supported by another study employing a second Nrf2/ARE pathway activator, Panax notoginseng saponins (46).…”
Section: The Neuroprotective Effects Of the Nrf2/are Pathway Againmentioning
confidence: 99%
“…Wu et al . reported that the Nrf2/ARE pathway activator myricetin lessened the production of ROS, decreased infarct volume, and reduced neuronal loss after ischemia (44, 45). This conclusion is supported by another study employing a second Nrf2/ARE pathway activator, Panax notoginseng saponins (46).…”
Section: The Neuroprotective Effects Of the Nrf2/are Pathway Againmentioning
confidence: 99%
“…Concomitantly, levels of pro-inflammatory cytokines were greatly reduced in the plasma and brain and oxygen-glucose deprived neuron/glia cultures. Further, using a mouse model of transient focal brain ischemia, Yao et al [92] showed that DMF and MMF (30 mg/kg i.p.) significantly reduced neurological deficits, infarct volume, brain edema, and cell death.…”
Section: Strokementioning
confidence: 99%
“…Additionally, DMF and MMF suppress glial activation following brain ischemia. Importantly, the protection of DMF and MMF was most evident during the sub-acute stage and was abolished in Nrf2 −/− mice, indicating that the Nrf2 pathway is required for the beneficial effects of DMF and MMF [92]. In another study, murine organotypic hippocampal slice cultures, and two neuronal cell lines were treated with DMF and MMF [93].…”
Section: Strokementioning
confidence: 99%
“…Since nonenzymatic substances (e.g., melatonin and ursolic acid) can detoxify ROS [62], and antioxidant enzymes (e.g., superoxide dismutase) and catalase (CAT) have effects on scavenging superoxide radicals; declined levels of those antioxidants negatively affect health in varying degrees [63,64]. Inhibition or lack of nuclear factor erythroid 2-related factor (Nrf2) which recognizes the antioxidant response element (ARE) and protects cells from ROS accumulation may increase injury to patients; however, this can be reversed by administration of antioxidants [65], such as dimethyl fumarate and monomethyl fumarate [66]. It is therefore not surprising that alterations in OS and anti-OS levels are found in ischemic CVD and depression as discussed earlier.…”
Section: Oxidative Stress and Antioxidativementioning
confidence: 99%